Seven‐year‐olds' references to internal states when playing with toy figures and a video game. Issue 3 (9th March 2021) - Hashmi, Salim; Paine, Amy L.; Hay, Dale F.
Abstract: References to internal states (e.g., thoughts, feelings, and desires) indicate children's appreciation of people's inner worlds. Many children spend time playing video games; however, the nature of children's speech when doing so has received little attention. We investigated the use of internal state language (ISL) as 251 seven‐year‐olds played with toy figures and a video game designed for the study. Although children used ISL more when playing with toy figures, children used ISL in both contexts, highlighting video game play as a context where children demonstrate their appreciation of inner worlds. Children's speech in the two contexts differed in how ISL was used: references to children's own internal states were more common when playing the video game, and the characters' internal states more common when playing with the toy figures. These findings are discussed with reference to the format of the play activities affording different opportunities to discuss internal states. Highlights: In traditional play children refer to internal states, however, it is unclear whether this occurs when they play video games. Children referred to internal states when playing with toy figures and a video game, but did so more with the toys. Children's video game play can be used as a new context for the study of children's social understanding.